Pengembangan Media Booklet Berbasis Keanekaragaman Jenis Jamur Makroskopis - Linna Fitriani; Yuni Krisnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to develop a booklet media based on the diversity of macroscopic mushroom species in Lubuklinggau City. The method used is the Research and Development (R&D) method, with two stages of research namely making media booklets and validating media booklets. Data collection using the JAS method. The validity of the booklet with questionnaires for media experts and material experts. Response readability and practicality using a questionnaire questionnaire lecturers and students, knowing the response to the effectiveness of the booklet by looking at learning outcomes with tests. Data analysis techniques using content analysis Validity Ratio (CVR). The results of stage 1 research found that there were 32 types of macroscopic fungi, from 4 classes, 9 orders, and 16 families. Fungi that can be consumed include Auricularia-auricula-juda, A. cornea, Schizophyllum commune, Lentinus strigosus, L. triginus, Favolus brasiliensis, F. tenuiculus, Pleuretus ostreatus, Agaricus silvaticus, Marasmius oreades, Tremella mesentere, Cook and Cavina tricholoma While the potential as a drug are Cordyceps militaris and Coprinellus disseminatus, and the type of poisonous mushroom is Chlorophyllum molybdites. The results of the analysis and validation of the media booklet of each criterion received a CVR value of 1.00 with valid or proper information. The lecturer and student questionnaire data for the average attractiveness of 3.3 were categorized as attractive, for readability 3.1 was categorized as good, for efficiency 3.5 was categorized very efficient, and for practicality an average of 3.7 was categorized very practical. In conclusion, the booklet that was developed was declared suitable for use, the booklet was categorized as attractive, good legibility, efficient and practical to use. Keywords: booklet, macroscopic mushroom, lubuklinggau, development